How physicians affect patients' employment outcomes through deciding on sick leave durations - Alexander Ahammer (Johannes Kepler University of Linz, Department of Economics, 2016)
I analyze how general practitioners (GPs) indirectly affect their patients' employment outcomes by deciding on the length of sickness absences. I use an instrumental variables framework where spell durations are identified through supply-side certification measures estimated from the data. I find that a marginal day of sick leave - that is, a day of sick leave which is only certified because a worker's GP has a high propensity to certify sick leaves - decreases employment probabilities persistently by 0.45 percentage points - 0.69 percentage points up to 18 months after the sick leave. Conversely, the risk of becoming unemployed increases by 0.28 percentage points - 0.44 percentage points due to the additional day of sick leave. These effects are mostly driven by men with comparably low job tenure and migratory background. Several robustness checks show that identification is not impaired by endogenous matching between patients and GPs. My results bear important implications for doctors: Whenever medically justifiable, it may be beneficial to certify shorter sick leaves in order to protect employment status of the patient.
Keywords: I10; J21; J60; 330; Sick leave duration; employment; general practitioners; supply-variation